Analysis of an English Teacher Talk in the Classroom Interaction at MTs Humaira Kota Bengkulu - Gressia Julia Eriz; Fera Zasrianita; Hanura Febriani (Journal of Innovation in Teaching and Instructional Media, 2025)
This study explores the types of talk used by an English teacher during classroom interaction at MTs Humaira Kota Bengkulu and examines how these strategies facilitate student engagement. Using a qualitative descriptive method, data were collected through classroom observation, interviews, and documentation. The findings indicate that the teacher employed various communicative strategies, such as praising, asking questions, giving directions, and incorporating students’ ideas resulting in increased participation and understanding. The teacher also utilized code-switching, tone modulation, and strategic gestures to support student comprehension. The novelty of this research lies in its specific focus on classroom discourse within the madrasah context, which has been underrepresented in previous studies. This research contributes to a deeper understanding of how teacher-led interaction fosters a more dynamic and interactive English learning environment in religious-based schools.